An analog of Hardy’s theorem for the second Hankel-Clifford transformation - amma, Mohamed El H; Daher, Radouan; Lahmadi, Hasnaa (Jurnal Matematika, Statistika dan Komputasi, 2022)
In this paper, we generalize theorem of Hardy for the second Hankel- Clifford transform .